THE INFLUENCE OF AUTHENTIC LEADERSHIP ON TURNOVER INTENTION WITH WORK ENGAGEMENT AS A MEDIATING VARIABLE - Ariska Dewi, Ni Putu (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
This research seeks to explore the impact of authentic leadership on turnover intention, with work engagement acting as a mediating variable, at Pecatu Guest House. The study is based on Social Exchange Theory. The pupulation consisted of 40 employees, with saturated sampling employed, resulting in a total of 40 respondents. Data analysis was performed using path analysis, classical assumption tests, and the mediation testing method proposed by Hair et al. (2017). The results indicate that authentic leadership has a significant negative effect on turnover intention. Moreover, authentic leadership has a positive and significant impact on work engagement, while work engagement exerts a significant negative influence on turnover intention. Additionally, work engagement functions as a competitive partial mediator in the relationship between authentic leadership and turnover intention. This study offers important insights and recommendations for Pecatu Guest House to evaluate and enhance its leadership approach in order to reduce employee turnover within the organization.